Study on Internal Gear Honing Stone Dressing and Gear Honing Technology based on Variable Axis Cross Angle - Xia Lian; Wang Dongling; Yuan Bin; Han Jiang (Jixie chuandong)
The honing stone profile shift coefficient will become negative by fixed axis cross angle when dressing honing stone,which change the gear honing contact condition and cutting parameters. Firstly,the gear surface structure formation mechanism and the causes of honing stone profile shift by fixed axis cross angle are analyzed. Then,a variable axis cross angle technology strategy of honing stone dressing is puts forward,which can guarantee the gear surface honing structure constant. It can be described that the axis cross angle is a function of center distance when honing stone dressing and gear honing. Finally,the simulation shows that the technology can obtain constant contact and cutting parameters between workpiece and honing stone during its life,and the surface structure of the gear will not change. At the same time,it can ensure that honing stone profile remains constant in its life,and the number of dressing times of honing wheel is greatly increased.